2002
DOI: 10.1524/ract.2002.90.9-11_2002.537
|View full text |Cite
|
Sign up to set email alerts
|

Sorption behaviour of Am on precorroded HLW glass in water and brines

Abstract: In the alteration layer of HLW glasses corroded in aqueous solutions, less soluble elements like REE, actinides and other elements are retained by sorption or by formation of secondary alteration products controlling the solution concentrations. In order to quantify the sorption effect on the retention of metal ions, first sorption tests with U, Th and Eu have been performed using precorroded, simulated HLW glass as substrate.To demonstrate that the sorption behaviour of Eu is also representative for homologue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Eventually, after contact with groundwater, clay minerals will form as secondary phases upon alteration of the waste matrix, e.g. HLW borosilicate glass, in the course of the geochemical evolution of the repository system over long periods of time (Abdelouas et al, 1997;Luckscheiter and Nesovic, 2002). Dissolution of various compounds of the multi-barrier system and subsequent reprecipitation of secondary clay minerals may occur.…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, after contact with groundwater, clay minerals will form as secondary phases upon alteration of the waste matrix, e.g. HLW borosilicate glass, in the course of the geochemical evolution of the repository system over long periods of time (Abdelouas et al, 1997;Luckscheiter and Nesovic, 2002). Dissolution of various compounds of the multi-barrier system and subsequent reprecipitation of secondary clay minerals may occur.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that uranium ions can be incorporated into haematite 229 and that radioactive iodine is adsorbed from solution by colloidal ferric hydroxide. 230 Other studies have investigated the adsorption of thorium on cement 231 and on ammonium molydophosphate, 232 of americium on glass 233 and of strontium-85 and -89 by rotting tree bark and similar biomass materials. 234…”
Section: Adsorption Of Radionuclidesmentioning
confidence: 99%
“…Eventually, if the waste matrix gets into contact with ground water, clay minerals may form as secondary phases upon alteration of the waste matrix in the course of the geological evolution of the repository system (Abdelouas et al, 1997;Luckscheiter et al, 2002). For example, the trioctahedral sme ctite hectorite has been identified in long ^term corrosion experiments as one of the secondary phases forming in the alteration layer of HLW glass under near ^field conditions (Zwicky et al, 1989).…”
Section: Introductionmentioning
confidence: 99%